(untitled) (Ustozlar uchun, 2026)
This article demonstrates that professional translation competence is a complex and multifaceted concept that requires a combination of linguistic, cultural, technical, and cognitive skills. In the modern globalized world, translators are expected not only to have a high level of language proficiency but also to effectively use digital tools and adapt to various translation contexts. The article explores the key components of translation competence, including linguistic accuracy, intercultural awareness, subject-specific knowledge, and technological literacy. It also examines the role of computer-assisted translation (CAT) tools, terminology management systems, and machine translation in improving translation quality and efficiency. In addition, the study highlights essential translation techniques such as equivalence, adaptation, and localization, which are necessary for producing accurate and culturally appropriate translations. The findings emphasize the importance of continuous professional development for translators in order to meet the increasing demands of the translation industry.